Usulan Penerapan Total Productive Maintenance pada Mesin Turbin Gas - Irnanda Pratiwi (Jurnal Optimasi Sistem Industri, 2019)
Overall Equipment Effectiveness (OEE) is one of the tools to enhance the effectiveness of the utilization rate of machinery and equipment in Total Productive Maintenance (TPM). TPM is a principle of management to improve productivity and efficiency of the production company to use the machine effectively. This study measures the value of OEE on gas turbine engine Centaur 50 C3344 which held on operation and maintenance section in PT Perta Samtan Gas Kilang Ekstraksi NGL Prabumulih in the period, followed by analyzing the value of using Pareto analysis of the results obtained by the root causes of the OEE. The conclusion that the value of the analysis results obtained on average exceeded the standard value of OEE 85.63% from 85%, even though in one period the value of OEE less than standard (22.63%). Factors that may experience rapid drop predicted loss is breakdown losses 382 hours (46.53%) and idling minor stoppages 373 hours (45.43), reduce speed 48 hours or 5.85%, rework losses 13 hours or 1.58%, and set up and adjustment losses 5 hours or 0.61%. As a result of which may not have an impact in a short time, but will immediately attack the machine if there is no treatment of maintenance as continuously and directly.